Construção e validação de cartilha educativa para promoção da saúde visual de crianças em idade escolar - Barreto, Ana Cristina Oliveira (2019)
The objective was to develop and validate an educational booklet to guide professionals, family members and teachers on promoting the visual health of school-aged children. Methodological study, with a quantitative approach, divided into two stages from June 2018 to March 2019. The first stage corresponds to the construction of the booklet, based on the content of an educational video validated in a previous study. The second corresponds to the validation of the educational booklet, being subdivided into content and appearance validation with specialists in the field of health and printed technologies and appearance validation with education specialists. The sample consisted of 24 specialists. This stage took place in a round and for evaluation an instrument that was already validated was used. In the appearance validation stage with education specialists, the sample consisted of 21 elementary school teachers 1 and a two-part instrument was used to assess the technology. The data obtained were organized in Excel and analyzed using statistical software. Descriptive statistics were used for absolute and relative frequencies. To analyze the agreement in the stages of validation of educational technology with all the specialists, Cronbach's alpha and binomial tests were used, respectively. The booklet was the first to be developed with a specific visual health theme for schoolchildren with a focus on teachers. With regard to the Flesch's Legibility Index, the booklet was classified as “very easy”, with a rate of 90%. Regarding the indicators evaluated by specialists in health and printed technology, all items went beyond the stipulated agreement. All 25 items evaluated within the six domains were classified as valid. Nineteen items received 24 (100%) positive responses (p = 0.005), which were statistically significant. Six items had 23 (95.8%) responses considered positive (p = 0.033). However, considering the improvement of technology, changes were still made based on the recommendations. The teachers considered the educational booklet validated in relation to the other indicators evaluated. It reached an agreement level equal to or greater than 81% and a general Cronbach's alpha of 0.79. Such results show that the technology built is reliable and valid to be used with teachers. The booklet therefore becomes relevant to be used as a health promotion strategy.